Improvements within the Scope of Ecological Design: Dadia Ecotourism Area (Greece) - Kısa Ovalı, Pınar; Tachir, Gildis (International Journal of Contemporary Economics and Administrative Sciences, 2018)
It is not right to evaluate the ecological design concept that includes past, present and future perspectives only with new building designs that comply with ecological principles. Improving existing ecological measures, improving their space comfortefficiency is of utmost importance for optimum utilization and conservation of resources. From this point of action, Dadia one of the major ecological tourism areas of Greece is presented with suggestions for improvement and development in terms of ecological design. In this sense, ecological design and ecological tourism related assumptions are explaining and supporting the current situation of ecological tourism center in accordance with the Dadia analyzing. The use of renewable energy sources in the existing service, the transport of vehicles with high CO2 emissions in the tourist area and transport problems for disabled people have been identified. A solution proposal was established within the framework of ecological design measures for these basic problems. The results of the study are specific to the field and provide an idea applicable to the ecological improvement of an existing area.